セッピョウ ヒョウソウ メカニカル ドリル ノ セッサク トクセイ - 藤井, 理行; フジイ, ヨシユキ; 田中, 洋一; タナカ, ヨウイチ; 成田, 英器; ナリタ, ヒデキ; 宮原, 盛厚; ミヤハラ, モリアツ; 高橋, 昭好; タカハシ, アキヨシ; Fujii, Yoshiyuki; Tanaka, Yoichi; et al. (1988)
P(論文) 氷床深層コア掘削用のドリル開発に関連して, メカニカルドリルの切削特性を把握するため, 表層コア掘削用の軽量メカニカルドリルの室内掘削試験を行った。得られたデータを, 切削理論に基づいて考察し, 次の結果を得た。(1)メカニカルドリルの消費エネルギーのうち, 1/3が切削に, 2/3がドリルの回転に使われる。(2)切削エネルギーは氷のせん断角が大きいほど小さくなるので, 効率のよい切削には, 刃のすくい角を大きくし, 刃先荷重を適切に調整する必要がある。また, (3)掘削時の消費エネルギーや刃先荷重のモニターにより, 氷床氷のせん断応力を連続的に測定できる可能性も示した。 A lightweight mechanical ice core drill of shallow depth capability was tested in a cold laboratory to obtain basic chracteristics of electromechanical drills in connection with a development of a deep ice core drilling system. We obtained the following results. (1) The total energy is consumed one-third for ice cutting and two-thirds for barrel rotation. (2) For efficient ice cutting, large rake angle and adequate edge load are essential. (3) Apossibility is shown for continuous measurement of shear stress of ice during ice coring. departmental bulletin paper